Implementasi Tangga Dramatik Dalam Dokumenter â€œDua Sisiâ€ Edisi â€œKami Dan Rumah Singgah Kebayaâ€ - Munggaran, Utari S S R; Asiatun, Siti (Jurnal Ilmiah Multimedia dan Komunikasi, 2024)
HIV or Human Immunodeficiency Virus is a type of virus that infects white blood cells which causes a decrease in human immunity. It had established a Rumah Singgah Kebaya. It is a non-governmental organization (NGO) in Yogyakarta that cares to HIV/AIDS patient. The NGO presents as a transgender empowerment center that provides shelter and assistance for People with HIV/AIDS (ODHA). In order to make visual documentary of the NGO, it was decided to create a television documentary program entitled "Dua Sisi" Edition of "Kami dan Rumah Singgah Kebaya". The methods used in the creation of this television documentary work are research methods, field observations, interviews with source persons, as well as television documentaries. This documentary applies the four stages of Aristotle's dramatic structure and to attract the attention of the audience through the dramatics implemented in the script so it is not monotonous. The dramatic structure has four stages as follows: Protasis Stage, Epitasio Stage, Catastasis Stage, and Catastrophe Stage. The type of this documentary work is a portrait documentary and its duration is about 22 minutes 35 seconds. Based on the analysis, it can be concluded that the dramatic structure is successfully implemented in the creation of this television documentary â€œDua Sisiâ€ Edisi â€œKami dan Rumah Singgah Kebayaâ€.